If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -2 = 4y + 14 Reorder the terms: -2 + 6y = 4y + 14 Reorder the terms: -2 + 6y = 14 + 4y Solving -2 + 6y = 14 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -2 + 6y + -4y = 14 + 4y + -4y Combine like terms: 6y + -4y = 2y -2 + 2y = 14 + 4y + -4y Combine like terms: 4y + -4y = 0 -2 + 2y = 14 + 0 -2 + 2y = 14 Add '2' to each side of the equation. -2 + 2 + 2y = 14 + 2 Combine like terms: -2 + 2 = 0 0 + 2y = 14 + 2 2y = 14 + 2 Combine like terms: 14 + 2 = 16 2y = 16 Divide each side by '2'. y = 8 Simplifying y = 8
| 3(x+5)+5+1=31 | | -2(4x-9)=10 | | 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 | | 4x=8x+32 | | x-0.7=5.5 | | 7x3/6 | | x*2x=50000 | | 3(2b-1)=27 | | 1/8x-1/8y=19 | | log(12)2+log(12)x=log(12)(x+7) | | 2x^3+12=0 | | -7-13=15 | | -4x+2y=34 | | 2x+7=-3x+8 | | (4x+7)=(7x-8) | | (6a^4b^3)(3ab^2)= | | X-4+12=12-2 | | 6xy*xy*4y= | | 2(4y-2)= | | (x+3)+(x-3)=1 | | (x+3)+(x-3)=0 | | 6(y+9)-56= | | 3x+11y=-7 |